The Main Factors in a Methodology for Evaluating Cooperation with Service Providers in HR Outsourcing - Małkus, Tomasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The expectations of organisations implementating HR outsourcing can differ significantly. Assumptions about the expected results of cooperation with a service provider substantially affect the assessment of the cooperation scheme. Depending on the importance of HR outsourcing in the strategy, assessment may be focused on the results achieved immediately after cooperation, but also in a longer strategic perspective. The purpose of this article is to present a methodology for evaluating cooperation in HR outsourcing. It considers the characteristics of the research area (cooperation with a specialised service provider), a course of conduct, examples of criteria and characteristics of selected tools that can be used in this field, including recommendations for their implementation.